Chapter L'autorappresentazione dei signori rurali (secoli XIV-XV): spunti di riflessione - Castelnuovo, Guido (Reti Medievali E-Book, 2023)
Is it possible to identify models of self-representation characteristic of rural lords in 14th-15th century Italy? Are these models common to the whole of the Peninsula, from the Alps to Sicily? What are their main features and their privileged channels of transmission? What relations do they have with the city-communal world on one hand, and princely cultures on the other? In order to answer these questions, the essay examines the use of a shared courtly culture, the importance of genealogical celebrations, the patronage and cultural enterprise of the lords and the growth of their direct intellectual dynamism, ending with the renewed importance of the castle in the cultural and social self-representation of the 15th-century lords.